Anti-Racism Education Based on Religious Moderation Values in Pesantren Salaf - Mustopa, Mustopa; Ridwan; Nasikhin, Nasikhin (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
This study aims to analyze the anti-racism education model based on religious moderation values in Pesantren. Using case study qualitative research, data were collected through in-depth interviews, observations, and documentation studies at Pesantren Nasrul Huda, Batang Regency. The data were analyzed using the Miles and Huberman model. The findings in this study show that the anti-racism education model is integrated through four indicators of religious moderation: tolerance, non-violence, adaptive to local culture, and love for the country. First, strengthening the tolerance aspect is realized through cross-cultural discussion programs and batsul masail activities, where santri are invited to understand different beliefs and customs as well as some cases of khilafiah in fiqh. Second, non-violence is taught through conflict resolution training and emotional management through queuing culture and the Qur'an memorization program, which helps students understand the importance of non-violent problem solving. Third, the formation of a person who is adaptive to local culture is strengthened by wayang art activities, cultural workshops, and the introduction of batik culture, such as learning traditional music. Fourth, love for the country is integrated through a program of visits to historical sites or social activities that foster a sense of love and pride in Indonesia. This pattern has succeeded in shaping the personalities of santri who lead to an appreciation of diversity and respect for others. This study contributes to finding an anti-racism education model based on religious moderation values to be applied in various salaf pesantren in Indonesia.